Protist impacts on marine cyanovirocell metabolism - Cristina Howard-Varona; Simon Roux; Benjamin P. Bowen; Leslie P. Silva; Rebecca Lau; Sarah M. Schwenck; Samuel Schwartz; Tanja Woyke; Trent Northen; Matthew B. Sullivan; Sheri A. Floge (ISME Communications, 2022)
Abstract The fate of oceanic carbon and nutrients depends on interactions between viruses, prokaryotes, and unicellular eukaryotes (protists) in a highly interconnected planktonic food web. To date, few controlled mechanistic studies of these interactions exist, and where they do, they are largely pairwise, focusing either on viral infection (i.e., virocells) or protist predation. Here we studied population-level responses of Synechococcus cyanobacterial virocells (i.e., cyanovirocells) to the protist Oxyrrhis marina using transcriptomics, endo- and exo-metabolomics, photosynthetic efficiency measurements, and microscopy. Protist presence had no measurable impact on Synechococcus transcripts or endometabolites. The cyanovirocells alone had a smaller intracellular transcriptional and metabolic response than cyanovirocells co-cultured with protists, displaying known patterns of virus-mediated metabolic reprogramming while releasing diverse exometabolites during infection. When protists were added, several exometabolites disappeared, suggesting microbial consumption. In addition, the intracellular cyanovirocell impact was largest, with 4.5- and 10-fold more host transcripts and endometabolites, respectively, responding to protists, especially those involved in resource and energy production. Physiologically, photosynthetic efficiency also increased, and together with the transcriptomics and metabolomics findings suggest that cyanovirocell metabolic demand is highest when protists are present. These data illustrate cyanovirocell responses to protist presence that are not yet considered when linking microbial physiology to global-scale biogeochemical processes.